The Risk of Meningitis Following Expanded Endoscopic Endonasal Skull Base Surgery: A Systematic Review - Lai, Leon T.; Trooboff, Spencer; Morgan, Michael K.; Harvey, Richard J. (Journal of Neurological Surgery Part B: Skull Base, 2014)
Objective To examine the risk of postoperative meningitis following expanded endoscopic endonasal skull base (EESB) surgery.Setting A systematic analysis of publications identified through searches of the electronic databases from Embase (1980–July 17, 2012), Medline (1950–July 17, 2012), and references of review articles.Main Outcome Measures Incidence of meningitis following EESB surgery.Results A total of 2,444 manuscripts were selected initially, and full-text analysis produced 67 studies with extractable data. Fifty-two contained data regarding the frequency of postoperative meningitis. The overall risk of postoperative meningitis following EESB surgery was 1.8% (36 of 2,005). For those reporting a cerebrospinal fluid (CSF) leak, meningitis occurred in 13.0% (35 of 269). For those not reporting a CSF leak, meningitis occurred in 0.1% (1 of 1,736). The odds ratio for the development of meningitis in the presence of a postoperative CSF leak was 91.99 (95% confidence interval, 11.72–721.88; p < 0.01). There was no difference in reported incidence of meningitis or CSF leak between anterior and posterior cranial fossa surgery. There was one reported case of meningitis-related mortality following EESB surgery.Conclusion The evidence in skull base surgery is limited. This study demonstrates a low incidence of meningitis (1.8%) following EESB procedures. The incidence of meningitis from EESB surgery without an associated CSF leak is uncommon.
Keywords: systematic review; endoscopy; endonasal; skull base; meningitis; CSF rhinorrhea